Dietary apigenin reduces LPS-induced expression of miR-155 restoring immune balance during inflammation - Arango, Daniel (Mol Nutr Food Res, 2015)
SCOPE: High incidence of inflammatory diseases afflicts the increasing aging-population infringing a great health burden. Dietary flavonoids, including the flavone apigenin, are emerging as important anti-inflammatory nutraceuticals due to their health benefits, lack of adverse effects and reduced costs. MicroRNAs (miRs) play a central role in inflammation by regulating gene expression, yet how dietary ingredients affect miRs is poorly understood. The aim of this study was to identify miRs involved in the anti-inflammatory activity of apigenin and apigenin-rich diets and determine their immune regulatory mechanisms in macrophages and in vivo. METHODS AND RESULTS: A high-throughput quantitative real-time PCR screen of 312 miRs in macrophages revealed that apigenin reduced LPS-induced miR-155 expression. Analyses of miR-155 precursor and primary transcript indicated that apigenin regulated miR-155 transcriptionally. Apigenin-reduced expression of miR-155, led to the increase of anti-inflammatory regulators FOXO3a and SMAD2 in LPS-treated macrophages. In vivo, apigenin or a celery-based apigenin rich diet reduced LPS-induced expression of miR-155 and decreased TNFα in lungs from LPS-treated mice. CONCLUSION: These results demonstrate that apigenin and apigenin-rich diets exert effective anti-inflammatory activity in vivo by reducing LPS-induced expression of miR-155, thereby restoring immune balance.